Acute toxicity of carbon dioxide to juvenile marine shrimp Litopenaeus vannamei (Boone 1931). Issue 4 (4th July 2017) - Furtado, Plínio S.; Gaona, Carlos A. P.; Serra, Fabiane P.; Poersch, Luis H.; Wasielesky, Wilson
ABSTRACT: Elevated concentrations of dissolved carbon dioxide (CO2 ) and reduced pH levels are observed during the culture and transportation of aquatic organisms. Studies on the toxicity effects of CO2 in penaeid shrimp are scarce when compared to the amount of research in fish. The objective of the present study was to determine the lethal concentration and safety levels of CO2 for juvenile white shrimp Litopenaeus vannamei . Juveniles (1.76 ± 0.36 g) were exposed for 96 h to one of six concentrations of dissolved CO2 (14.5, 23.8, 59.0, 88.0, 115.0, and 175.0 mg/L) or a control condition (without the addition of CO2 ), and their survival was monitored for 96 h. The LC50 values with 95% confidence limits at 24, 48, 72, and 96 h were 130.05 (104.2–162.1), 77.2 (73.8–80.02), 69.65 (65.47–74.32), and 59.12 (53.08–66.07) mg/L of CO2, respectively. The calculated safety level was 5.9 mg/L of CO2, and the highest concentration that did not induce significantly higher mortality than that observed in controls (NOEC) was 23.8 mg/L of CO2 . We recommend that CO2 levels should be kept below the safety level obtained in this study.